2003
DOI: 10.1083/jcb.200308110
|View full text |Cite
|
Sign up to set email alerts
|

Cophosphorylation of amphiphysin I and dynamin I by Cdk5 regulates clathrin-mediated endocytosis of synaptic vesicles

Abstract: It has been thought that clathrin-mediated endocytosis is regulated by phosphorylation and dephosphorylation of many endocytic proteins, including amphiphysin I and dynamin I. Here, we show that Cdk5/p35-dependent cophosphorylation of amphiphysin I and dynamin I plays a critical role in such processes. Cdk5 inhibitors enhanced the electric stimulation–induced endocytosis in hippocampal neurons, and the endocytosis was also enhanced in the neurons of p35-deficient mice. Cdk5 phosphorylated the proline-rich doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
231
7
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(246 citation statements)
references
References 36 publications
7
231
7
1
Order By: Relevance
“…As a result of this work, it has been shown that dynamin 1 was significantly reduced not only in the hippocampus of an AD mouse model and in cultured hippocampal neurons treated with Aβ but also in the brain of AD patients (Yao et al 2003;Kelly et al 2005;Kelly and Ferreira 2006). The mechanisms leading to this dynamin 1 depletion seem to involve calpain, a protease system that is active in AD (Tsuji et al 1998;Lee et al 2000;Battaglia et al 2003;Tomizawa et al 2003;Chen and Fernandez 2005;Demuro et al 2005;Gong et al 2005;Kelly et al 2005;Fifre et al 2006;Kelly and Ferreira 2006). Furthermore, we have reported that this Aβ-mediated dynamin 1 degradation was the result of calpain activation induced by the sustained calcium influx mediated by N-methyl-D-aspartate (NMDA) receptors in hippocampal neurons (Kelly and Ferreira 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this work, it has been shown that dynamin 1 was significantly reduced not only in the hippocampus of an AD mouse model and in cultured hippocampal neurons treated with Aβ but also in the brain of AD patients (Yao et al 2003;Kelly et al 2005;Kelly and Ferreira 2006). The mechanisms leading to this dynamin 1 depletion seem to involve calpain, a protease system that is active in AD (Tsuji et al 1998;Lee et al 2000;Battaglia et al 2003;Tomizawa et al 2003;Chen and Fernandez 2005;Demuro et al 2005;Gong et al 2005;Kelly et al 2005;Fifre et al 2006;Kelly and Ferreira 2006). Furthermore, we have reported that this Aβ-mediated dynamin 1 degradation was the result of calpain activation induced by the sustained calcium influx mediated by N-methyl-D-aspartate (NMDA) receptors in hippocampal neurons (Kelly and Ferreira 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII/JNK and calcineurin/NFAT-induced up-regulation of Fas/FasL is involved in cell apoptosis (40,41). In addition, activated calcineurin may be involved in the endocytosis of kainate receptors through the dephosphorylation of endocytic proteins such as amphiphysin I and dynamin I (42,43). In our experiments, kainate-evoked [Ca 2+ ] i and reduced membrane expression of GluK2 were observed simultaneously; therefore, we speculate that Ca 2+ /calmodulinactivated calcineurin may induce kainate receptor endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Unlike other cell cycle-promoting members of Cdk family, Cdk5 kinase primarily modulates neuroskeletal dynamics in postmitotic neurons. 3,7,8 Cdk5 plays an essential role in both developing and adult neurons, including neuronal migration, 9,10 axon guidance, 11 neurite outgrowth, 7 dynamics of synaptic structure, [12][13][14] neurotransmission, 15,16 and neuronal secretion. 17 Cdk5 null mice suffer perinatal mortality, with severe defects in neuronal migration and laminar configuration in the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%